Internal Audit Effectiveness and Financial Accountability in the Provincial Treasuries of South Africa - Msindwana, Modjadji Charlotte; Ngwakwe, Collins C. (International Journal of Economics and Financial Issues, 2022)
Provincial Treasuries are responsible for assisting the National Treasury in enforcing compliance with the measures established in the South African constitution, which stipulates public sector expenditure control and transparency. This study aims to examine the relationship between internal audit effectiveness and financial accountability in the Provincial Treasuries of South Africa. The theoretical inclination is on the stewardship theory. The research is based on a quantitative approach and draws secondary data on internal audit and financial performance from the nine provincial treasuries of South Africa. Analyses were done using the fixed effect regression after conduction the Hausman tests, Augmented Dickey-Fuller tests (ADF) and Philips Perron (PP). Findings indicate that internal audit can enhance financial accountability across all the expenditure programmes of provincial treasuries in South Africa. Government departments should embrace internal audit as a monitoring tool to evaluate financial accountability and service delivery performance, but not as a punitive initiative. In addition, educational training of internal audit staff can be very effective in achieving government financial control. The paper provides a veritable case study to higher institutions regarding educational qualification versus experience implications on public sector internal audit and accountability; it also offers an agenda for further research.